Disputes Related to the Insurance Contract in Algerian Law - Chahrazed, Kadem Souad; Sofiane , Kadem (Journal of Ecohumanism, 2025)
The insurance contract, like any other contract, gives rise to disputes between the parties when executed. These disputes are often resolved amicably between the insurer (the insurance company) and the insured, either through compensation provided by the insurer to the insured in the event that the value is simply estimated, or if this is not possible, the insurance company may call upon experts to carry out this process. Alternatively, the parties may resort to the judiciary if amicable solutions fail, and in such cases, local and specialized jurisdictional rules must be respected, otherwise, the lawsuit will be rejected.